2007
DOI: 10.9755/ejfa.v12i1.5175
|View full text |Cite
|
Sign up to set email alerts
|

The response of slow-growing chicks to the supplementations with different methionine levels and/or two types of enzymes

Abstract: In order to study productive performance and meat quality of slow-growing chicks used for rural poultry production in relation to methionine and enzyme supplementations, basal diets were formulated to contain 0.32, 0.29 and 0.27% methionine levels from 1 to 42 d of age, 43 to 84 d of age, and 85 to 98 d of age, respectively. These diets were supplemented with 0, 0.06 and 0.12% of DL-methionine; thus, there were three methionine levels during each period. These levels were fed with or without 750 FTY of phytase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Research suggests slow-growing broilers may be better suited to free-range and pasture poultry systems than their fast-growing counterparts ( Rack et al., 2009 ). Some studies found slow-growing broilers to have better meat quality, and lower nutrient requirements and cost of rearing ( Attia et al., 2007 , 2009 , 2011 , 2017 ). To date, Australia has not conducted research into developing any specific slow-growing broiler breed.…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests slow-growing broilers may be better suited to free-range and pasture poultry systems than their fast-growing counterparts ( Rack et al., 2009 ). Some studies found slow-growing broilers to have better meat quality, and lower nutrient requirements and cost of rearing ( Attia et al., 2007 , 2009 , 2011 , 2017 ). To date, Australia has not conducted research into developing any specific slow-growing broiler breed.…”
Section: Introductionmentioning
confidence: 99%
“…There was no significant difference between enzymes supplemented diets or probiotics supplemented ones when comparison was made within or over different tested sources. The increase in dry matter digestibility could enhance ME value of the diet, and increase ME availability for growth (Jeroch et al, 1995;Cowan et al, 1996;Zanella et al1999, Ghazalah et al, 2005and Attia et al 2007. However, Rebolé et al (1999) reported that enzyme addition to broiler diets containing 15% sunflower meal did not significantly improved digestibility of protein/amino acid, fat/fatty acids and ME.…”
Section: Apparent Digestibility Of Nutrients and Ash Retentionmentioning
confidence: 99%
“…Protein conversion ratio was calculated by dividing protein intake by body weight gain. Coefficient of apparent digestibility of nutrients of the total gut was calculated according to Attia et al (2007) using three replicates of one male each/ treatment. At 49 wk of age, 3 chicks were taken randomly from each treatment, and slaughtered; the remaining carcass after bleeding, was plucked and eviscerated then weighed (dressed weight) and divided into chest and hind parts and weighed.…”
Section: Experimental Design Birds and Dietsmentioning
confidence: 99%
“…The probiotics supplemented group was also efficiently (p≥0.05) better than the enzyme cocktail containing phytase. The improved performance of enzymes supplemented group could be attributed to better digestibility of nutrients, limit antinutritional factors, better gut health and immune response (Jeroch et al, 1995;Zanella et al, 1999;Kocher et al, 2002;Saleh et al, 2003;Yonemochi et al, 2003;Choct, 2006;Selle et al, 2006;Attia et al, 2007;. On the other hand, the effect of probiotics could be explained by the effect of probiotics on gut health and elimination of the harmful substances including the indetectable level of mycotoxicns due to its contents of Bacillus subtillis fermentation extract, Brewers yeast extract, lactic acid, citric acid, calcium propionate, sodium aluminosilicate and DLmethionine.…”
Section: Growth Performancementioning
confidence: 99%
“…Protein conversion ratio was calculated by dividing protein intake by body weight gain for the whole experimental period. Coefficient of apparent digestibility of nutrients of the total gut was calculated according to Attia et al (2007) using three replicates of one male each/ treatment. At 7 wk of age, 3 chicks were taken randomly from each treatment, and slaughtered; the remaining carcass after bleed, plucked and eviscerated was weighed (dressed weight) and divided into front and hind parts and weighed.…”
Section: Criteria Of Responsementioning
confidence: 99%